Tingkat Ketergantungan (Usability) E-learning di Fakultas Saitek UIN Walisongo Semarang - Adzhal Arwani Mahfudh; Favian Agung Rizki; Ahilla Salma Alfaza (Universitas Islam Negeri Walisongo Semarang, 2020)
Utilizing technology, especially the internet to support the teaching and learning process, is what happened in the 21st century. E-learning is one of the learning innovations in the network that allows users to access material or collect assignments online. The benefits of e-learning are so numerous and can help lectures, users can access anywhere without being limited by space and time. The method used is descriptive research, which in its implementation consists of data collection, analysis and interpretation of the meaning of the data obtained. . This study aims to determine the level of usability or usability that exists on the e-leraning website of UIN WALISONGO Saintek Faculty, whether the system has been made that meets the usability criteria or not, in terms of Learnability, Efficiency, Memorability, Errors, and Satisfaction. After conducting research, the authors obtain data that e-learning meets usability criteria seen from the data in the field that is the result of the survey. So, Walisongo e-learning can be used as a support for learning effectively and efficiently.